The Effect of Vocabulary Mastery on Student’s Writing Skill - Puji Anto; Tri Anita (Candradimuka: Journal of Education, 2023)
This research is aimed to get empirical data and analyze the effect of vocabulary mastery on student’s writing recount (survey at private senior high schools in Central Jakarta). This research is done by Descriptive statistics, Kolmogorov-Smirnov test to test the normality, and Anova Table. The research was held at Private Senior High Schools in Central Jakarta. Data collective done by giving test for vocabulary mastery (multiple-choice and words matching / 20 items) and test for writing descriptive text given to tenth grade students. Due to the result, it can be inferred that there is an effect of vocabulary mastery towards student’s writing recount text (Sig = 0.000 and t test = 5.336; while t table = 1.68), (the correlation coefficient = 0.805 and the coefficient determination = 64.9%).